2010
DOI: 10.2224/sbp.2010.38.8.1041
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Undergraduate Student Athletes: The Roles of Perfectionism and Trait Anxiety on Perception of Procrastination Behavior

Abstract: The purpose in this study was to examine how undergraduate student athletes organized different explanations relating to behavioral procrastination into a hierarchy. Participants (N = 201) completed the State-Trait Anxiety Inventory (Spielberger, Gorsuch, Lushene, Vagg, & Jacobs, 1983) and the Multidimensional Perfectionism Scale (Hewitt & Flett, 1991) personality questionnaires. Two groups (low and high trait-anxious and perfectionist) were created from the lower and upper third responses. These participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…Finally, finding indicated that individuals with a high level of procrastination report significantly greater level of overall difficulties in regulating their emotions. According to previous studies, the higher level of procrastination is associated with greater experience of negative emotion (whether as an antecedent or as a consequence) ( Chabaud et al, 2010 ; Patrzek et al, 2012 ), which exacerbates the need to use strategies to recover their emotions. Result also indicated that DERS-Strategies was the only dimension which remained significant after controlling for anxiety and depression.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, finding indicated that individuals with a high level of procrastination report significantly greater level of overall difficulties in regulating their emotions. According to previous studies, the higher level of procrastination is associated with greater experience of negative emotion (whether as an antecedent or as a consequence) ( Chabaud et al, 2010 ; Patrzek et al, 2012 ), which exacerbates the need to use strategies to recover their emotions. Result also indicated that DERS-Strategies was the only dimension which remained significant after controlling for anxiety and depression.…”
Section: Discussionmentioning
confidence: 96%
“…Students who procrastinate are more likely to experience depression and social anxiety than students who don’t procrastinate ( Mohammadi Bytamar et al, 2017 ). Procrastination is also associated with experiences of persistent stress and negative emotions, including anxiety, distress, depression, and hopelessness ( Chabaud et al, 2010 ; Sirois, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the tendency to procrastinate has less effect on the relationship between reading strategies and information avoidance. Negative emotions and personality traits (Clark and Hill, 1994) such as anxiety, disturbance, depression, and disappointment (Aziz and Tariq, 2013; Cassady and Johnson, 2002; Chabaud et al, 2010; Owens and Newbegin, 1997; Solomon and Rothblum, 1984) vis-a-vis stress, frustration, feelings of annoyance, indecision decisions, and task avoidance (Grunschel et al, 2013; Kliengsiek et al, 2013) have been identified as factors of procrastination. In this study, 20% of the respondents indicated that they spend one to two hours (120 minutes) searching for journal articles on a daily basis on top of the other priorities and activities they have within the day.…”
Section: Discussionmentioning
confidence: 99%
“…Звертаючись до вивчення психологічного змісту структури особистості прокрастинатора, науковці акцентують увагу на різних аспектах. Деякі з них зосереджуються на емоційних переживаннях (Chabaud, Ferrand & Maury, 2010), які супроводжують подібне зволікання, водночас у межах інших праць головним об'єктом наукового пошуку стає спосіб мислення (Karas & Spada, 2009) або ж особливості поведінки (Van Eerde, 2003) осіб, схильних до відкладання важливих справ.…”
Section: рис 1 інтегральна модель особистості прокрастинатораunclassified